Activities of crisis centers in providing social assistance to women affected by domestic violence - Agnė Maričevaitė; Neringa Povilaitienė (Taikomieji Moksliniai Tyrimai, 2023)
The article analyzes the activity of a social worker in a crisis center working with women who experience domestic violence. Based on the results of the research, the functions and roles of the social worker, social services provided in the crisis center were analyzed. Based on the analysis of scientific information sources and after conducting a structured interview survey, the aim was to determine the types of violence experienced by women, aspects of cooperation with other institutions. Difficulties experienced by the social worker when working in the crisis center with women who have experienced domestic violence have been identified.